Improved rat liver decellularization by arterial perfusion under oscillating pressure conditions. (4th September 2014) - Struecker, Benjamin; Butter, Antje; Hillebrandt, Karl; Polenz, Dietrich; Reutzel‐Selke, Anja; Tang, Peter; Lippert, Steffen; Leder, Anne; Rohn, Susanne; Geisel, Dominik; Denecke, Timm; Aliyev, Khalid; et al.
Abstract: One approach of regenerative medicine to generate functional hepatic tissue in vitro is decellularization and recellularization, and several protocols for the decellularization of livers of different species have been published. This appears to be the first report on rat liver decellularization by perfusion under oscillating pressure conditions, intending to optimize microperfusion and minimize damage to the ECM. Four decellularization protocols were compared: perfusion via the portal vein (PV) or the hepatic artery (HA), with (+P) or without (–P) oscillating pressure conditions. All rat livers ( n = 24) were perfused with 1% Triton X‐100 and 1% sodium dodecyl sulphate, each for 90 min with a perfusion rate of 5 ml/min. Perfusion decellularization was observed macroscopically and the decellularized liver matrices were analysed by histology and biochemical analyses (e.g. levels of DNA, glycosaminoglycans and hepatocyte growth factor). Livers decellularized via the hepatic artery and under oscillating pressure showed a more homogeneous decellularization and less remaining DNA, compared with the livers of the other experimental groups. The novel decellularization method described is effective, quick (3 h) and gentle to the extracellular matrix and thus represents an improvement of existing methodology. Copyright © 2014 John Wiley & Sons, Ltd.